A double stamp on indigenous early Roman Empire pottery from Dessobriga (Osorno, Palencia / Melgar, Burgos) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
An unpublished, at first view epigraphic, double stamp on Early Roman Empire Vaccean pottery found at the archaeological site of Dessobriga (Osorno la Mayor, Palencia / Melgar de Fernamental, Burgos), in course of excavation since 2014. Context of the find, epigraphic study and restoration process.
Keywords: Dessobriga; Archaeological site; Vaccean pottery; Celtiberian pottery; Early Empire pottery; Pottery stamp; Celtiberian epigraphy; Latinisation of the Vaccean territory; Writing in Vaccean territory; Restauration of ancient pottery